Enhancing functional expression of heterologous lipase in the periplasm of Escherichia coli - Xu, Y. L.; Yasin, A.; Wucherpfennig, T.; Chou, C. P. (World Journal of Microbiology & Biotechnology, 2008)
Functional expression of heterologous Pseudozyma antarctica lipase B (PalB) in the periplasm of Escherichia coli was explored using four fusion tags, i.e. DsbC, DsbA, maltose-binding protein (MBP), and FLAG in the sequence of increasing expression efficacy. Amongst these fusion tags, FLAG and MBP appear to be the most effective ones in terms of boosting enzyme activity and enhancing solubility of PalB, respectively. Overexpression of these PalB fusions often resulted in concomitant formation of insoluble inclusion bodies. Coexpression of a selection of periplasmic folding factors, including DegP (and its mutant variant of DegP(S210A)), FkpA, DsbA, DsbC, and a cocktail of SurA, FkpA, DsbA, and DsbC, could improve the expression performance. Coexpression of DsbA appeared to be the most effective in reducing the formation of inclusion bodies for all the four PalB fusions, implying that functional expression of PalB could be limited by initial bridging of disulfide bonds. Culture performance was optimized by overexpressing FLAG-PalB with DsbA coexpression, resulting in a high volumetric PalB activity of 360 U/L.